STRATEGI PELAYANAN MUTU PAUD UNTUK MENINGKATKAN ANIMO MASYARAKAT DI PAUD CITRA HARAPAN KECAMATAN UNGARAN BARAT - Sri Janji; Noor Miyono (STKIP Subang, 2024)
The aim of this research is to determine PAUD quality service strategies in order to increase community interest in Citra Harapan PAUD, West Ungaran District. This type of research is qualitative research. The research was carried out at Citra Harapan PAUD, West Ungaran District because this PAUD is a private PAUD which must have alternative strategies for quality services to increase public interest in sending their children to PAUD. Data collection methods were carried out by interviews, documentation and observation. Data analysis uses the data triangulation method. Based on the results of the data analysis, the following conclusions were obtained: (1) The PAUD quality service strategy in order to increase community interest in Citra Harapan PAUD, West Ungaran District is quite optimal, both in terms of providing quality PAUD. (2) The elements of quality PAUD have been fulfilled including: quality of the learning process, partnership with parents, existence of services that monitor the fulfillment of essential needs of early childhood (outside of education), leadership and resource management and quality human resource support as well as various The excellence of the school is the